The back-deposition of dissolved Mn2+ to MnO2 cathodes for stable cycling in aqueous zinc batteries. Issue 31 (28th March 2022) - Yang, Xianpeng; Jia, Zhongqiu; Wu, Wanlong; Shi, Hua-Yu; Lin, Zirui; Li, Cuicui; Liu, Xiao-Xia; Sun, Xiaoqi
Abstract : The back-deposition of dissolved Mn 2+ is a key factor for stable cycling of MnO2 cathodes in aqueous zinc batteries. Abstract : The Mn 2+ dissolution of MnO2 cathode materials causes rapid capacity decay in aqueous zinc batteries. We herein show that the dissolved Mn 2+ can be deposited back to the cathode with the aid of a suitable conductive agent. The active material is thus retained for energy storage, and this MnO2 /Mn 2+ redox process also provides capacity. In the Mn 2+ free ZnSO4 electrolyte, MnO2 delivers 325 mA h g −1 capacity at 0.1 A g −1, and 90.4% capacity retention is achieved after 3000 cycles at 5 A g −1 . Our work demonstrates an effective strategy to realize stable cycling of MnO2 cathodes in aqueous zinc batteries without Mn 2+ additives.